2016
DOI: 10.1111/pedi.12475
|View full text |Cite
|
Sign up to set email alerts
|

Alternate glycemic markers reflect glycemic variability in continuous glucose monitoring in youth with prediabetes and type 2 diabetes

Abstract: Objective To determine whether the alternate glycemic markers, fructosamine (FA), glycated albumin (GA), and 1,5-anhydroglucitol (1,5AG), predict glycemic variability captured by continuous glucose monitoring (CGM) in obese youth with prediabetes and type 2 diabetes (T2D). Study Design Youth with BMI ≥85th%ile, 10-18 years, had collection of fasting plasma glucose (FPG), hemoglobin A1c (HbA1c), FA, GA, and 1,5AG and 72 hours of CGM. Participants with HbA1c ≥5.7% were included. Relationships between glycemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 60 publications
1
20
0
1
Order By: Relevance
“…1) showed that the addition of liraglutide improved glycemic control compared with CSII alone, manifested by decreased FBG and estimated HbA1c. As previous studies have shown, 1,5-AG is a new clinical marker for glycemic control in patients with type 2 diabetes [23,24]. In this study, we found that the serum 1,5-AG concentration in the CSII combined with liraglutide group was significantly higher than that in the CSII alone group (Table 2), which may further imply that glycemic control with CSII combined with liraglutide is better than with CSII.…”
Section: Discussionsupporting
confidence: 62%
“…1) showed that the addition of liraglutide improved glycemic control compared with CSII alone, manifested by decreased FBG and estimated HbA1c. As previous studies have shown, 1,5-AG is a new clinical marker for glycemic control in patients with type 2 diabetes [23,24]. In this study, we found that the serum 1,5-AG concentration in the CSII combined with liraglutide group was significantly higher than that in the CSII alone group (Table 2), which may further imply that glycemic control with CSII combined with liraglutide is better than with CSII.…”
Section: Discussionsupporting
confidence: 62%
“…Hemoglobin A1c, while a convenient method for diabetes screening in a community health setting does have significant variability, even within the standardization program. The use of A1c compared with other methods of diabetes screening such as fasting glucose or 2‐hour oral glucose tolerance testing may identify different populations of youth 18‐20 . An elevated A1c value repeated in a short time interval could lead to 2 different categories (LRPD, HRPD, or diabetes) simply based on the variability of the A1c measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The use of A1c compared with other methods of diabetes screening such as fasting glucose or 2-hour oral glucose tolerance testing may identify different populations of youth. [18][19][20] An elevated A1c value repeated in a short time interval could lead to 2 different categories (LRPD, HRPD, or diabetes) simply based on the variability of the A1c measurement. This variability highlights the importance of repeat testing.…”
Section: Limitationsmentioning
confidence: 99%
“…Our group previously found that alternate glycemic markers correlate with multiple continuous glucose monitoring (CGM) variables (17) and that these markers are sensitive for detecting type 2 diabetes in obese youth with prediabetes (14). Therefore, we enrolled participants with CF and a group of healthy control subjects (HCs) into a studydthe Glycemic Monitoring in Cystic Fibrosis Study (GeM-CF)d aimed at characterizing free-living glucose patterns across the glycemic spectrum and have collected alternate markers of glycemia in this cohort.…”
mentioning
confidence: 99%